Anti-aging and anti-cracking organic silicon stone protective material as well as preparation method and application thereof
By introducing phenyl-modified organosilicon oligomer materials, the problems of easy cracking, poor permeability, and insufficient high-temperature and UV aging resistance of alkoxysilane protective materials have been solved, achieving efficient reinforcement and protection of stone cultural relics.
Patent Information
- Application Number
- CN202511291293.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2026-01-06
AI Technical Summary
Existing alkoxysilane protective materials are prone to cracking during the gelation process, which leads to a decrease in protective effect. They also have problems such as poor permeability, insufficient high temperature resistance and UV aging resistance.
Phenyl-modified organosilicon oligomers are introduced to improve the heat resistance and UV aging resistance of the material through the phenyl structure, and to reduce internal stress concentration during the gelation process, forming a three-dimensional network cross-linked layer to enhance the structural density of stone artifacts.
It significantly improves the thermal and UV stability of the material, reduces the risk of cracking during the gelation process, enhances the compressive strength and weather resistance of stone artifacts, and maintains the original appearance without affecting the artifacts' appearance.
Smart Images

Figure CN121270925A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of cultural relic protection, and particularly relates to an aging-resistant and anti-cracking organic silicon stone protection material, a preparation method and application thereof. BACKGROUND
[0002] Stone cultural relics, as an important carrier of human civilization, bear irreplaceable historical, artistic and scientific values. However, long-term exposure to the natural environment, stone cultural relics face multiple threats such as physical weathering, chemical corrosion, biological erosion and the like. Weathering leads to loose structure, strength decline and surface pulverization, which is the main form of deterioration of stone cultural relics. For example, the sandstone of Yungang Grottoes is easy to be eroded by water and salted out due to high porosity and low cement content, leading to surface peeling and deep cracking. Acid rain and industrial pollution further accelerate this process, making cultural relic protection a global problem to be solved.
[0003] At present, alkoxysilane materials (such as tetraethyl orthosilicate TEOS) are the mainstream choice for stone cultural relic protection. It forms a silicon-oxygen network by hydrolysis and condensation, fills the pores and enhances the structure. However, such materials have the following inherent defects: easy cracking, the pure silicon-oxygen network (such as TEOS self-polymer) has a high volume shrinkage rate of up to 30% during gelation, leading to internal stress concentration and forming micro-cracks; the silicon-oxygen network formed by condensation of alkoxysilane is too hydrophilic and easy to absorb water, which aggravates the damage of freeze-thaw cycle.
[0004] To solve the problem of cracking and excessive hydrophilicity of traditional alkoxysilane protective materials during gelation, researchers have proposed various modification methods. Escalante M et al. found that the cracking of alkoxysilane protective materials was the result of competition between shrinkage driven by capillary pressure (Escalante M, Valenza J, Scherer G W. 9th Int. Con. on the Deterioration and Conservation of Stone [C]. Amsterdam: Elsevier, 2000: 459-46.) and the elastic modulus of the gel itself (Yang M, Scherer G W, Wheeler G S. Compatible Materials for the Protection of European Cultural Heritage [R]. Athens: PACT 56 (Tech. Chamber Greece), 1998: 201-208.). As evaporation proceeds, the shrinkage deformation caused by capillary pressure becomes larger and larger, eventually leading to cracking. Adding nanoparticles such as SiO2 or TiO2 can release the problem of capillary pressure during gelation and enhance mechanical strength (Luo Hongjie, Liu Rong, Huang Xiaoxiao. Research Progress on Anti-cracking of Organic Silicon Materials for Stone Cultural Heritage Protection [J]. China Materials Progress, 2012, 31(11): 1-8.). Introducing surfactants to improve the cracking problem during gelation, Xu et al. used N-octane as a catalyst and hexadecyltrimethoxysilane (HDTMS) as a waterproof additive to obtain a macroporous gel network protective agent, which did not crack (Xu Feigao, Li Dan, Zhang Hean, et al. TEOS / HDTMS Inorganic-Organic Hybrid Compound Used for Stone [J]. Journal of Sol-Gel Science and Technology, 2012, 61(2): 429-435.).The introduction of organic flexible segments can also improve the cracking problem during the gelation process. In the 1980s, Rhone-Poulenc added methylphenyl silicone oil or dimethyl silicone oil to ethyl silicate to obtain commercialized and improved RC80 and RC90 with reduced cracking (Scherer G W, Wheeler GS. Silicate Consolidants for Stone [J]. Key Engineering Materials, 2009(391): 1-25.); Mackenzie et al. introduced PDMS elastic segments into orthosilicate, such as polydimethylsiloxane (PDMS) segments, to improve the flexibility of the material and prevent cracking (Mackenzie J D. Structures and Properties of Ormosils [J]. Journal of Sol-Gel Science & Tech, 1994(2): 81-86.).
[0005] The materials developed to solve the cracking problem of traditional alkoxysilane protective materials during the gelation process have their own advantages, but also have various problems. The introduction of nanoparticles releases the capillary pressure during the gelation process and prevents cracking during the gelation process, but the introduction of nanoparticles may reduce the permeability of the protective material. The introduction of surfactants can improve the cracking problem in the short term, but the surfactants contain metal ions or other soluble salts, which can cause salting-out and accelerate the deterioration of stone materials if left inside the stone cultural relics (George WScherer. Crystallization in Pores [J]. Cement and Concrete Research, 1999(29): 1347-1358.). The introduction of organic flexible segments into alkoxysilane materials can greatly improve the cracking problem of the material, but the organic groups can cause the aging resistance of alkoxysilane protective materials to decline, limiting the protective effect (Xiang L, Li X, Zhang Y Q, et al. Research Progress on Degradation Behavior of Silicone Materials [J / OL]. New Chemical Materials, 1-8.).
[0006] Therefore, to solve the cracking problem of alkoxysilane protective materials and improve the permeability, high temperature resistance, and ultraviolet aging resistance of alkoxysilane protective materials, a new material needs to be designed and synthesized, which should have good anti-cracking, easy penetration, high temperature resistance, and ultraviolet aging resistance. Once it penetrates into stone cultural relics, it can have a good reinforcing effect. SUMMARY
[0007] The purpose of this invention is to provide an aging-resistant and crack-resistant organosilicon protective material, its preparation method, and its application, in order to solve at least one of the problems mentioned above, namely, affecting material penetration, accelerating stone deterioration, and having limited protective effect. This solution introduces phenyl groups to form phenyl-modified organosilicon oligomers, achieving excellent high-temperature and UV aging resistance, as well as addressing the cracking problem during the gelation process.
[0008] The objective of this invention is achieved through the following technical solution:
[0009] The first aspect of this invention discloses an aging-resistant and crack-resistant organosilicon protective material having the structure shown in formula (I):
[0010]
[0011] In formula (I):
[0012] R1 is -CH3, -CH2CH3 and One of them, where y is a positive integer between 1 and 300;
[0013] R2 is -CH3, -CH2CH3, -NH2、 and One of them, z is a positive integer between 0 and 300.
[0014] Preferably, y is a positive integer between 5 and 150; and / or, z is a positive integer between 0 and 100.
[0015] The second aspect of this invention discloses a method for preparing the aging-resistant and crack-resistant organosilicon protective material as described above, comprising the following steps:
[0016] a) Stir and mix tetraethyl orthosilicate, phenylalkoxysilane and methylalkoxysilane until homogeneous to obtain a mixed reaction solution;
[0017] b) Add solvent and acid catalyst to the mixed reaction solution and heat to react. After cooling to room temperature, the organosilicon protective material is obtained.
[0018] Preferably, in step a), the phenylalkoxysilane has the structure shown in formula (II):
[0019]
[0020] In formula (II): R3 is either methyl or ethyl.
[0021] Preferably, in step a), the methylalkoxysilane has the structure shown in formula (III):
[0022]
[0023] In formula (III): R3 is either methyl or ethyl.
[0024] Preferably, in step b), the solvent is at least one of water, ethanol, tetrahydrofuran, acetone and ethyl acetate; and / or, the acid catalyst is at least one of dilute hydrochloric acid, dilute sulfuric acid and acetic acid; and / or, the reaction temperature of the heating reaction is 50-80°C and the reaction time is 1-24 h.
[0025] Preferably, in step b), the solvent is at least one of water and ethanol, and the total molar degree of hydrolysis of the reactant monomer in the solvent is 80-100%; and / or, the reaction temperature of the heating reaction is 65-75°C, and the reaction time is 4-16 h.
[0026] The third aspect of this invention discloses the application of the aging-resistant and crack-resistant organosilicon protective material described above in the reinforcement of silicate cultural relics, wherein the reinforcement of silicate cultural relics is carried out through the following steps:
[0027] The organosilicon protective material is prepared as a solution, applied to silicate artifacts, allowed to stand and solidify, and then catalyzed by the addition of organic amines, causing the organosilicon protective material to gel on the surface and inside of the silicate artifacts, forming a three-dimensional network cross-linked layer.
[0028] Preferably, the solution has a mass content of 10-30%; and / or, the solvent of the solution is at least one of water, ethanol, tetrahydrofuran, acetone and ethyl acetate; and / or, the material of the silicate artifact includes sandstone, red sandstone, glazed tiles, pottery, porcelain and brick; and / or, the static curing time is 1-30 days.
[0029] Preferably, the organic amine is at least one selected from triethylamine, ammonia, n-octylamine, and γ-aminopropyltriethoxysilane; and / or, the amount of the organic amine added is 0.01-5% of the mass of the organosilicon protective material.
[0030] The working principle of this invention is as follows:
[0031] The phenyl-modified organosilicon oligomers provided by organosilicon protective materials, due to the presence of phenyl groups, exhibit excellent high-temperature resistance and UV aging resistance due to their conjugated structure and high bond energy.
[0032] This phenyl-modified organosilicon oligomer protective material significantly improves its thermal and UV stability by introducing aromatic groups. The high bond energy of the carbon-carbon bonds in its phenyl molecular structure, combined with the conjugation effect, effectively slows down the degradation process of side-chain organic groups and inhibits the generation of macromolecular free radicals, thereby reducing the risk of silicon-oxygen backbone breakage. The material's molecule contains abundant reactive groups (such as hydroxyl and alkoxy groups), endowing it with good solubility, low system viscosity, and high chemical reactivity. Compared to traditional alkoxysilane materials, this system exhibits superior high-temperature stability and UV resistance.
[0033] As a difunctional siloxane structure, its chain segments exhibit excellent flexibility, which can solve the cracking problem during the gelation process; at the same time, this phenyl organosilicon oligomer can easily penetrate into the interior of stone artifacts, strengthening them.
[0034] During the penetration process, the silanol groups contained in this protective material can undergo a condensation reaction with the hydroxyl groups on the stone surface, forming a three-dimensional network cross-linked layer in the porous structure. This structural feature allows it to uniformly cover the pore surface of the stone, effectively bridging loose mineral particles and enhancing the density of the stone's internal structure.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) By introducing a phenyl structure, the heat resistance and UV stability of the material are improved, effectively resisting aging factors in the natural environment.
[0037] (2) The presence of phenyl side group functional groups improves the flexibility of the material and reduces internal stress concentration during the gelation process, thereby reducing the risk of cracking.
[0038] This material can be formulated into a solution, which penetrates and undergoes a condensation reaction with the hydroxyl groups on the surface of the stone to form a three-dimensional network cross-linked layer, thus reinforcing the stone artifacts. The reinforced stone artifacts not only exhibit significantly improved compressive strength but also demonstrate excellent resistance to high temperatures and ultraviolet aging, while maintaining their original appearance, in accordance with the principle of minimal intervention in cultural relic preservation. Attached Figure Description
[0039] Figure 1 The FT-IR spectrum of the phenyl-modified organosilicon oligomer prepared in Example 1;
[0040] Figure 2 The FT-IR spectrum of the gel after gelation of the phenyl-modified organosilicon oligomer prepared in Example 1 is shown.
[0041] Figure 3 Thermogravimetric analysis spectrum of the phenyl-modified organosilicon oligomer prepared in Example 1;
[0042] Figure 4 The DTG analysis spectrum of the phenyl-modified organosilicon oligomer prepared in Example 1;
[0043] Figure 5 The water contact angle of the phenyl-modified organosilicon oligomer reinforced sandstone prepared in Example 1 and the water contact angle of the reinforced sandstone after xenon lamp aging;
[0044] Figure 6 The FT-IR spectrum of the organosilicon oligomer prepared in Comparative Example 1 is shown below.
[0045] Figure 7 The FT-IR spectrum of the gel after gelation of the organosilicon oligomer prepared in Comparative Example 1 is shown.
[0046] Figure 8 Thermogravimetric analysis spectrum of the organosilicon oligomer prepared in Comparative Example 1;
[0047] Figure 9 The DTG analysis spectrum of the organosilicon oligomer prepared in Comparative Example 1;
[0048] Figure 10 This is a comparison image of the gel after gelation of the phenyl-modified organosilicon oligomer prepared in Example 1 and the gel after gelation of the organosilicon oligomer prepared in Comparative Example 1.
[0049] Figure 11 The water contact angle of the organosilicon oligomer reinforced sandstone prepared for Comparative Example 1 and the water contact angle of the reinforced sandstone after xenon lamp aging. Detailed Implementation
[0050] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. However, the embodiments are not intended to limit the scope of protection of the present invention. All raw materials used in the embodiments can be commercially available or prepared using conventional methods.
[0051] This invention addresses the problems in the prior art by preparing a phenyl-modified organosilicon oligomer material (i.e., organosilicon stone protective material): 1. Nanoparticles reduce the permeability of the protective material; 2. Surfactants accelerate the deterioration of stone; 3. Organic groups lead to a decrease in the aging resistance of alkoxysilane protective materials. This material has excellent advantages such as crack resistance, easy permeability, high temperature resistance, and UV aging resistance, and can achieve a good reinforcement effect once it penetrates into stone cultural relics.
[0052] This phenyl-modified organosilicon oligomer material has a Si-O-Si chain backbone and the structure shown in formula (I):
[0053]
[0054] In formula (I):
[0055] R1 represents directly linked organic functional groups in the molecule, and y represents the number of siloxane units containing repeating phenyl groups, i.e., the degree of polymerization of the polymer; specifically, R1 is -CH3, -CH2CH3, etc. and One of them, where y is a positive integer between 1 and 300, preferably a positive integer between 5 and 150;
[0056] R2 represents directly linked organic functional groups in the molecule, and z represents the number of repeating silicon-oxygen linkages, i.e., the degree of polymerization of the polymer; specifically, R2 is -CH3, -CH2CH3, etc. -NH2、 and One of them, z is a positive integer between 0 and 300, preferably a positive integer between 0 and 100.
[0057] The phenyl-modified organosilicon oligomer protective material exhibits an initial thermal degradation temperature of 300–495°C in thermogravimetric analysis, and a color difference value of ΔE of 1–15 in a 300°C heat resistance test.
[0058] This phenyl-modified organosilicon oligomer protective material significantly improves its thermal and UV stability by introducing aromatic groups. The high bond energy of the carbon-carbon bonds in its phenyl molecular structure, combined with the conjugation effect, effectively slows down the degradation process of side-chain organic groups and inhibits the generation of macromolecular free radicals, thereby reducing the risk of silicon-oxygen backbone breakage. The material's molecule contains abundant reactive groups (such as hydroxyl and alkoxy groups), endowing it with good solubility, low system viscosity, and high chemical reactivity. Compared to traditional alkoxysilane materials, this system exhibits superior high-temperature stability and UV resistance.
[0059] It is worth noting that during the penetration process, the silanol groups in this protective material can undergo a condensation reaction with the hydroxyl groups on the stone surface, forming a three-dimensional network cross-linked layer in the porous structure. This structural feature allows it to uniformly cover the pore surface of the stone, effectively bridging loose mineral particles and enhancing the density of the stone's internal structure. The reinforced stone artifacts not only exhibit significantly improved compressive strength but also demonstrate excellent high-temperature resistance and UV aging resistance, while maintaining their original appearance, thus conforming to the principle of minimal intervention in cultural relic preservation.
[0060] The preparation method of this phenyl-modified organosilicon oligomer material includes the following steps:
[0061] (1) Add tetraethyl orthosilicate, phenylalkoxysilane and methylalkoxysilane to the reaction vessel and stir to mix them evenly;
[0062] (2) Add solvent and acid catalyst to the reaction vessel and heat up to carry out the reaction;
[0063] (3) After the reaction is completed, the reactants are cooled to room temperature to obtain the phenyl-modified organosilicon oligomer.
[0064] The structural formula of phenylalkoxysilane is shown in formula (II):
[0065]
[0066] The structural formula of methylalkoxysilane is shown in formula (Ⅲ):
[0067]
[0068] In formulas (II) and (III): R3 is either methyl or ethyl.
[0069] Preferably, the solvent used in the reaction is at least one of water, ethanol, tetrahydrofuran, acetone, and ethyl acetate, and more preferably at least one of water and ethanol.
[0070] Preferably, the acid catalyst is at least one of dilute hydrochloric acid, dilute sulfuric acid, and acetic acid.
[0071] Preferably, the reaction system is heated to 50–80°C and the reaction time is 1–24 h; more preferably, the reaction temperature is 65–75°C and the reaction time is 4–16 h.
[0072] The chemical reaction equation for preparing phenyl-modified organosilicon oligomers is shown below:
[0073]
[0074] The method of using this phenyl-modified organosilicon oligomer material in protecting silicate cultural relics is as follows:
[0075] The phenyl-modified organosilicon oligomer is prepared into a phenyl-modified organosilicon oligomer solution with a mass percentage of 10-30% using a solvent. This solution is then applied to the silicate artifact to be reinforced and allowed to stand for curing. If necessary, 0.01-5% organic amine can be added to catalyze the solution and promote the gelation process, forming a phenyl-modified organosilicon gel on the surface and inside of the silicate artifact.
[0076] As a preferred option, silicate artifacts are selected from one of the following: sandstone from the Yungang Grottoes, fragile red sandstone, glazed tiles from ancient buildings, pottery, porcelain, and bricks.
[0077] Preferably, the solvent is at least one of water, ethanol, tetrahydrofuran, acetone, and ethyl acetate.
[0078] Preferably, the organic amine is at least one of triethylamine, ammonia, n-octylamine, and γ-aminopropyltriethoxysilane.
[0079] Preferably, the static curing time is 1 to 30 days.
[0080] The silicate artifacts protected and reinforced with phenyl-modified organosilicon oligomers exhibit the following characteristics: color difference ΔE≤5, compressive strength 20–35 MPa, ultrasonic velocity 1.8–2.5 km / s, Leeb hardness 200–280 HL, water contact angle 70–95°, and air permeability 50–200 g·m³. -2 24h -1 .
[0081] Example 1
[0082] To a dry 250 mL three-necked flask, add 0.1 mol (approximately 19.8 g) of methylphenyldimethoxysilane and 0.1 mol (approximately 20.8 g) of tetraethyl orthosilicate sequentially. Then add 0.52 mol (approximately 24 g) of anhydrous ethanol. Place the flask on a magnetic stirrer and stir at 800 rpm for 10 minutes to ensure thorough mixing of the raw materials. Slowly add 0.1 mol / L hydrochloric acid solution, controlling the dropping rate, until the total molar degree of hydrolysis of the monomer reaches 100%. After the addition is complete, attach a reflux condenser to the three-necked flask and place it in an oil bath. Raise the reaction temperature to 70 °C and maintain this temperature, stirring at 800 rpm for 12 hours. After the reaction is complete, allow the system to cool to room temperature, then add 5% (by mass) of triethylamine from the total sol mass and continue stirring for 10 minutes to ensure uniform dispersion of the triethylamine in the system. The sandstone sample was then immersed in the system for 5 minutes and allowed to stand at room temperature (25°C) for 21 days to solidify, eventually gelling.
[0083] The sol and gel were tested using Fourier transform infrared spectroscopy (FT-IR), and the FT-IR spectral results are shown in the attached figure. Figure 1 , 2 As shown in the figure. Thermogravimetric analysis (TGA) was used to perform thermogravimetric testing on the gel, and the results are attached. Figure 3 , 4 As shown. A universal testing machine was used to test the compressive strength. The test results showed that the compressive strength of the reinforced weathered sandstone increased to 30.39 MPa. A colorimeter was used to measure the color of the weathered sandstone samples before and after reinforcement. The test results showed that the color difference value ΔE was 3.29, which did not affect the color of the reinforced sandstone and met the principles of cultural relic protection. A depth-of-field microscope was used to observe the gel surface, and no gel cracking was observed. A xenon lamp aging tester was used to conduct a full-spectrum aging test on the sandstone reinforced in Example 1; simulating outdoor natural climate aging, the test conditions were as follows: irradiance 550 W / m². 2The aging time was 168 hours, the temperature was 20℃, and the relative humidity was 70%. The changes in the water contact angle of the sandstone before and after aging are as follows: Figure 5 As shown, the sandstone reinforced with the organosilicon protective material of this scheme exhibits essentially no change in water contact angle after aging, indicating that silicate cultural relics reinforced with this organosilicon protective material have good UV resistance (radiation resistance). Water was used as a control sample in the permeability test of the sandstone, and the permeability depth results are shown in Table 1 below.
[0084] Table 1. Results of water penetration depth in Example 1
[0085] Materials H2O Example 1 Penetration depth (mm) 18.12 16.03
[0086] It is evident that the permeability of the organosilica protective material in sandstone is essentially equivalent to that of water, meaning that the organosilica protective material in this solution possesses excellent permeability.
[0087] Example 2
[0088] To a dry 250 mL three-necked flask, add 0.05 mol (approximately 9.9 g) of methylphenyl dimethoxysilane, 0.05 mol (approximately 11.8 g) of 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane, and 0.1 mol (approximately 20.8 g) of tetraethyl orthosilicate sequentially. Then add 0.52 mol (approximately 24 g) of anhydrous ethanol. Place the flask on a magnetic stirrer and stir at 800 rpm for 10 minutes to ensure thorough mixing of the reactants. Slowly add 0.1 mol / L hydrochloric acid solution, controlling the dropping rate, until the total molar degree of hydrolysis of the monomer reaches 100%. After the addition is complete, attach a reflux condenser to the three-necked flask, place it in an oil bath, raise the reaction temperature to 70 °C, and maintain this temperature while stirring at 800 rpm for 12 hours. After the reaction was complete, the system was cooled to room temperature. Triethylamine was added at 5% of the total mass of the sol, and the mixture was stirred for another 10 minutes to ensure that the triethylamine was evenly dispersed in the system. The sandstone sample was then immersed in the system for 5 minutes and allowed to stand at room temperature (25°C) for 15 days to solidify, eventually gelling.
[0089] The sol and gel were tested using Fourier transform infrared spectroscopy (FT-IR), which detected characteristic peaks of methylphenyl, epoxy, and Si-O-Si chemical bonds and groups in the gel. Thermogravimetric analysis (TGA) was used to evaluate the thermal stability of the gel. Compressive strength tests were conducted using a universal testing machine, and the results showed that the compressive strength of the reinforced weathered sandstone increased to 23.50 MPa. Colorimeter measurements were performed on the weathered sandstone samples before and after reinforcement, showing a color difference value ΔE of 4.8. Depth-field microscopy revealed no gel cracking on the gel surface.
[0090] Example 3
[0091] To a dry 250 mL three-necked flask, add 0.06 mol (approximately 11.88 g) of methylphenyl dimethoxysilane, 0.04 mol (approximately 4.8 g) of dimethyldimethoxysilane, and 0.1 mol (approximately 20.8 g) of tetraethyl orthosilicate sequentially. Then add 0.52 mol (approximately 24 g) of anhydrous ethanol. Place the flask on a magnetic stirrer and stir at 800 rpm for 10 minutes to ensure thorough mixing of the reactants. Slowly add 0.1 mol / L hydrochloric acid solution, controlling the dropping rate, until the total molar degree of hydrolysis of the monomer reaches 100%. After the addition is complete, attach a reflux condenser to the three-necked flask, place it in an oil bath, raise the reaction temperature to 75°C, and maintain this temperature while stirring at 800 rpm for 10 hours. After the reaction was complete, the system was cooled to room temperature. Triethylamine was added at 5% of the total mass of the sol, and the mixture was stirred for another 10 minutes to ensure that the triethylamine was evenly dispersed in the system. The sandstone sample was then immersed in the system for 5 minutes and allowed to stand at room temperature (25°C) for 7 days to solidify, eventually gelling.
[0092] The sol and gel were tested using Fourier transform infrared spectroscopy (FT-IR), which detected characteristic peaks of related chemical bonds and groups such as methylphenyl, Si-CH3, and Si-O-Si. Thermogravimetric analysis (TGA) was used to test the gel, showing good thermal stability. Compressive strength testing using a universal testing machine showed that the compressive strength of the reinforced weathered sandstone increased to 21.50 MPa. The water contact angle of the gel surface was measured using a contact angle meter, showing a water contact angle of 85°, indicating some hydrophobicity and relatively good air permeability. Colorimeter measurements of the weathered sandstone samples before and after reinforcement showed a color difference value ΔE of 3.9. Depth-field microscopy revealed no gel cracking.
[0093] Example 4
[0094] To a dry 250 mL three-necked flask, add 0.05 mol (approximately 9.9 g) of methylphenyldimethoxysilane, 0.05 mol (approximately 12.3 g) of 3-methacryloyloxypropylmethyldimethoxysilane, and 0.1 mol (approximately 20.8 g) of tetraethyl orthosilicate sequentially. Then add 0.52 mol (approximately 24 g) of anhydrous ethanol. Place the flask on a magnetic stirrer and stir at 800 rpm for 10 minutes to ensure thorough mixing of the reactants. Slowly add 0.1 mol / L hydrochloric acid solution, controlling the dropping rate, until the total molar degree of hydrolysis of the monomer reaches 100%. After the addition is complete, attach a reflux condenser to the three-necked flask, place it in an oil bath, raise the reaction temperature to 65 °C, and maintain this temperature while stirring at 800 rpm for 8 hours. After the reaction was complete, the system was cooled to room temperature. 5% ethylenediamine was added according to the total mass of the sol, and stirring was continued for 10 minutes to ensure that the ethylenediamine was evenly dispersed in the system. The sandstone sample was then immersed in the system for 5 minutes and allowed to stand at room temperature (25°C) for 8 days to solidify, eventually gelling.
[0095] The sol and gel were tested using Fourier Transform Infrared Spectroscopy (FT-IR), which detected characteristic peaks of related chemical bonds and groups such as methylphenyl, C=C, C=O, and Si-O-Si. Thermogravimetric analysis (TGA) was used to perform thermogravimetric analysis on the gel. Compressive strength was tested using a universal testing machine, and the results showed that the compressive strength of the reinforced weathered sandstone increased to 27.20 MPa. Colorimeter measurements were performed on the weathered sandstone samples before and after reinforcement. The results showed a color difference value ΔE of 4.9, indicating a slight color change due to double bond oxidation, but still meeting the requirement of ΔE ≤ 5. Depth-field microscopy was used to observe the gel surface, and no gel cracking was observed.
[0096] Example 5
[0097] To a dry 250 mL three-necked flask, add 0.08 mol (approximately 15.84 g) of methylphenyldimethoxysilane, 0.1 mol (approximately 20.8 g) of tetraethyl orthosilicate, and 0.02 mol (approximately 4.1 g) of γ-aminopropylmethyldiethoxysilane sequentially. Then add 0.52 mol (approximately 24 g) of anhydrous ethanol. Place the flask on a magnetic stirrer and stir at 800 rpm for 10 minutes to ensure thorough mixing of the reactants. Slowly add 0.1 mol / L hydrochloric acid solution, controlling the dropping rate, until the total molar degree of hydrolysis of the monomer reaches 100%. After the addition is complete, attach a reflux condenser to the three-necked flask, place it in an oil bath, raise the reaction temperature to 70 °C, and maintain this temperature while stirring at 800 rpm for 12 hours. After the reaction was complete, the system was cooled to room temperature. 5% ethylenediamine was added according to the total mass of the sol, and stirring was continued for 10 minutes to ensure that the ethylenediamine was evenly dispersed in the system. Then, the sandstone sample was immersed in the system for 5 minutes and allowed to stand at room temperature (25°C) for 10 days to solidify, eventually gelling.
[0098] Using Fourier Transform Infrared Spectroscopy (FT-IR) to test sols and gels, methylphenyl (700-800 cm⁻¹) can be detected. -1 ), amino (3300-3500cm) -1 ) and Si-O-Si (1000-1100cm) -1 Characteristic peaks were observed. Thermogravimetric analysis (TGA) was used to test the gel. Compressive strength was tested using a universal testing machine, and the results showed that the compressive strength of the reinforced weathered sandstone increased to 27.1 MPa. Colorimetry was used to measure the color of the weathered sandstone samples before and after reinforcement; the color difference value ΔE was 4.5, meeting the requirement of ΔE≤5. No gel cracking was observed when the gel surface was examined using a depth-of-field microscope.
[0099] Comparative Example 1
[0100] Add 0.1 mol (approximately 20.8 g) of tetraethyl orthosilicate to a dry 250 mL three-necked flask. Then add 0.26 mol (12.0 g) of anhydrous ethanol. Place the flask on a magnetic stirrer and stir at 800 rpm for 10 minutes to ensure thorough mixing. Slowly add 0.1 mol / L hydrochloric acid solution, controlling the addition rate, until the total molar hydrolysis degree of the monomer reaches 100%. After the addition is complete, attach a reflux condenser to the flask and place it in an oil bath. Raise the reaction temperature to 70°C and maintain this temperature, stirring at 800 rpm for 12 hours. After the reaction is complete, allow the system to cool to room temperature. Add 5% (by mass) of triethylamine to the system and continue stirring for 10 minutes to ensure uniform dispersion of the triethylamine. Then immerse a sandstone sample in the system for 5 minutes and allow it to solidify at room temperature (25°C) for 21 days, ultimately achieving gelation.
[0101] The sol and gel were tested using Fourier transform infrared spectroscopy (FT-IR), and the FT-IR spectral results are shown in the attached figure. Figure 6 , 7 As shown in the figure. Thermogravimetric analysis (TGA) was used to perform thermogravimetric testing on the gel, and the results are attached. Figure 8 , 9 As shown in the attached figure. A universal testing machine was used to test the compressive strength. The test results showed that the compressive strength of the reinforced weathered sandstone increased to 23.48 MPa. A colorimeter was used to measure the color of the weathered sandstone samples before and after reinforcement. The test results showed that the color difference value ΔE was 4.79, which did not affect the color of the reinforced sandstone and met the principles of cultural relic protection. A depth-of-field microscope was used to observe the gel surface, and gel cracking was observed, as shown in the attached figure. Figure 10 As shown in the figure. The sandstone reinforced in Example 1 was aged using a xenon lamp, and the changes in the water contact angle of the sandstone before and after aging are shown in the figure. Figure 11 As shown in Table 2, water was used as a control sample in the permeability test of sandstone, and the results of the permeation depth are shown below.
[0102] Table 2 shows the results of water infiltration depth in Comparative Example 1.
[0103] Materials H2O Comparative Example 1 Penetration depth (mm) 18.12 12.35
[0104] It is evident that the organosilicon oligomer prepared in Comparative Example 1 has significantly lower permeability in sandstone than water, and is also significantly lower than the phenyl-modified organosilicon oligomer prepared in Example 1. This indicates that the phenyl modification in this scheme can effectively improve the permeability of organosilicon stone protective materials in silicate cultural relics.
[0105] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. An aging- and cracking-resistant silicone-stone protective material, characterized by, has the following formula (I) structure: In formula (I): R1is one of -CH3, -CH2CH3, and y is a positive integer between 1 and 300. R2is -CH3, -CH2CH3, -NH2, one of -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH 2. The weathering and cracking resistant silicone stone protection material according to claim 1, characterized in that, Y is a positive integer between 5 and 150; and / or, z is a positive integer between 0 and 100.
3. A process for the production of an ageing- and cracking-resistant silicone-stone protective material as claimed in claim 1 or 2, characterized in that Comprising the following steps: a) stirring and mixing tetraethyl orthosilicate, phenylalkoxysilane and methylalkoxysilane uniformly to obtain a mixed reaction solution; b) adding a solvent and an acid catalyst to the mixed reaction solution and warming to react, and obtaining the silicone stone protection material after cooling to room temperature.
4. The method of claim 3, wherein the silicone stone protective material is prepared by mixing the silicone stone protective material with the aging-resistant and anti-cracking agent. In step a), the phenylalkoxysilane has the following formula (II) structure: In formula (II), R3 is one of methyl and ethyl.
5. The method of claim 3, wherein the silicone stone protective material is prepared by mixing the silicone stone protective material with a curing agent, and then curing the mixture. In step a), the methylalkoxysilane has the following formula (III) structure: In formula (III), R3 is one of methyl and ethyl.
6. The method of claim 3, wherein the silicone stone protective material is prepared by mixing the silicone stone protective material with a curing agent, and then curing the mixture. In step b), the solvent is at least one of water, ethanol, tetrahydrofuran, acetone and ethyl acetate; and / or, the acid catalyst is at least one of dilute hydrochloric acid, dilute sulfuric acid and acetic acid; and / or, the reaction temperature of the warming reaction is 50-80°C, and the reaction time is 1-24h.
7. The method of claim 3, wherein the silicone stone protective material is prepared by mixing the silicone stone protective material with a curing agent, and then curing the mixture. In step b), the solvent is at least one of water and ethanol, and the total molar hydrolysis degree of the reaction monomers in the solvent is 80-100%; and / or, the reaction temperature of the warming reaction is 65-75°C, and the reaction time is 4-16h.
8. Use of the ageing- and cracking-resistant silicone stone protection material according to claim 1 or 2 for the consolidation of silicate monuments, characterized in that, The reinforcement of the silicate cultural relics is carried out by the following steps: The silicone stone protection material is configured as a solution, the solution is applied to the silicate cultural relics, and the solution is cured and catalyzed by adding an organic amine, so that the silicone stone protection material is gelled on the surface and inside of the silicate cultural relics to form a three-dimensional network crosslinked layer.
9. Use according to claim 8, characterized in that, The mass content of the solution is 10-30%; and / or, the solvent of the solution is at least one of water, ethanol, tetrahydrofuran, acetone and ethyl acetate; and / or, the material of the silicate cultural relics includes sandstone, red sandstone, colored glaze tile, pottery, porcelain and brick; and / or, the curing time is 1-30 days.
10. Use according to claim 8, characterized in that, The organic amine is at least one of triethylamine, ammonia, n-octylamine and gamma-aminopropyltriethoxysilane; and / or, the mass addition amount of the organic amine is 0.01-5% of the mass of the silicone stone protection material.